SMRT sequencing data for Garcinia mangostana L. variety Mesta - Midin, Mohd Razik; Loke, Kok-Keong; Madon, Maria; Nordin, Mohd Shukor; Goh, Hoe-Han; Mohd Noor, Normah (2017)
The “Queen of Fruits” mangosteen (Garcinia mangostana L.) produces commercially important fruits with desirable taste of ﬂesh and pericarp rich in xanthones with medicinal properties. To date, only limited knowledge is available on the cytogenetics and genome sequences of a common variety of mangosteen (Abu Bakar et al., 2016 [1]). Here, we report the ﬁrst single-molecule real-time (SMRT) sequencing data from whole genome sequencing of mangosteen of Mesta variety. Raw reads of the SMRT sequencing project can be obtained from SRA database with the accession numbers SRX2718652 until SRX2718659.